Neural dynamics of pain modulation by emotional valence - Zidda, Francesca; Lyu, Yuanyuan; Nees, Frauke; Radev, Stefan T; Sitges, Carolina; Montoya, Pedro; Flor, Herta; Andoh, Jamila (Cerebral cortex, 2024)
Definitions of human pain acknowledge at least two dimensions of pain, affective and sensory, described as separable and thus potentially differentially modifiable. Using electroencephalography, we investigated perceptual and neural changes of emotional pain modulation in healthy individuals. Painful electrical stimuli were applied after presentation of priming emotional pictures (negative, neutral, positive) and followed by pain intensity and unpleasantness ratings. We found that perceptual and neural event-related potential responses to painful stimulation were significantly modulated by emotional valence. Specifically, pain unpleasantness but not pain intensity ratings were increased when pain was preceded by negative compared to neutral or positive pictures. Amplitudes of N2 were higher when pain was preceded by neutral compared to negative and positive pictures, and P2 amplitudes were higher for negative compared to neutral and positive pictures. In addition, a hierarchical regression analysis revealed that P2 alone and not N2, predicted pain perception. Finally, source analysis showed the anterior cingulate cortex and the thalamus as main spatial clusters accounting for the neural changes in pain processing. These findings provide evidence for a separation of the sensory and affective dimensions of pain and open new perspectives for mechanisms of pain modulation.
Online veröffentlicht: 6. September 2024
Gesehen am 21.10.2024